Biossorção de compostos fenólicos de bagaços de uva em Saccharomyces cerevisiae: mecanismos do processo e bioacessibilidade - Rubio, Fernanda Thaís Vieira (2017)
The biosorption of phenolic compounds from grape pomace by Saccharomyces cerevisiae represents a viable alternative to the reuse of these two industrial wastes discarded on a large scale and for the valorization of by-products through their transformation into valueadded items. Total phenolic compounds (TPC) from Cabernet Sauvignon and Bordeaux grape pomaces varieties were adsorbed by S. cerevisiae biomasses modified by chemical and thermal treatments. The evaluation of biosorption was based on kinetic study,equilibrium study, analysis of the interaction of TPC with the biosorbent, using mid-infrared attenuated total reflectance (MIR-ATR) and characterization techniques such as scanning electron microscopy (SEM), x-ray diffraction (XRD) and high performance liquid chromatography (HPLC). Extracts e suspensions of yeast were submitted to a gastrointestinal digestion simulated in vitro. The biosorption process followed a pseudosecond order model and yeasts modified with sulfuric acid and sodium hydroxide were the most efficient in biosorption of TPC from Bordeaux grape pomace extract (BE) and Cabernet Sauvignon grape pomace extract (CSE), respectively, once they showed higher sorption capacity. Temkin isotherm showed a better fit for the equilibrium data of biosorption of TPC from CSE in basic yeast whereas sorption data of TPC from BE in acid yeast were best described by the Dubinin-Radushkevich model. There was a significant difference between treated and control yeasts and these biomasses before and after biosorption, with the exception of the yeast thermally treated. The yeasts and extracts characterization showed that the biomasses were enriched with phenolic compounds because of changes in biomasses and extracts after biosorption. The in vitro digestion study demonstrated that the biosorption is capable to cause an increase in the bioaccessibility of bioactive compounds present in extracts after biosorption and enriched yeasts displays an important role in the preservation of the antioxidant activity and bioaccessibility of adsorbed compounds.